Prevalence and pattern of hand eczema in a tertiary referral hospital of Nepal - Shrestha, Rushma; Karki, Anupama (Grande Medical Journal, 2019)
Background: Hand eczema is a very common condition that has a significant effect on an individual’s life in terms of daily functioning including various occupations. Studies show that the point prevalence of hand eczema is around 4% and the lifetime prevalence is 15%. Objective: The objective of this study is to determine the prevalence and pattern of hand eczemas in patients attending the Dermatology outpatient department of Bir hospital. Materials and methods: This is a retrospective study, where all the cases of hand eczema who presented to the Dermatology Out-Patient Department of Bir Hospital during the period from Baisakh 2075 till Chaitra 2075 B.S were recorded. Results: Eczema was diagnosed in 5,100 new cases (15.74%) and among them, hand eczema was seen in 494 cases, which accounts for 9.68% of all eczemas. The mean age was 37.43 years. Out of all the hand eczemas recorded, 334 (67.6%) were unspecified hand eczemas, pompholyx was seen in 92 (18.6%) cases, chronic hand eczema in 27 (5.5%), contact dermatitis in 20 (4%) patients and finger tip eczema was seen in 15 (3%) cases. Conclusion: Hand eczema is one of the common dermatological conditions. Our study showed the prevalence of hand eczema to be 9.68%.